2023
DOI: 10.1111/1541-4337.13146
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of polyphenol oxidase in tea (Camellia sinensis): Physiological characteristics, oxidation manufacturing, and biosynthesis of functional constituents

Abstract: Polyphenol oxidase (PPO) is a metalloenzyme with a type III copper core that is abundant in nature. As one of the most essential enzymes in the tea plant (Camellia sinensis), the further regulation of PPO is critical for enhancing defensive responses, cultivating high-quality germplasm resources of tea plants, and producing tea products that are both functional and sensory qualities. Due to their physiological and pharmacological values, the constituents from the oxidative polymerization of PPO in tea manufact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 200 publications
0
8
1
Order By: Relevance
“…Additionally, the organic acids accumulated continue to reduce pH late in the withering stage, which prevented the enzyme from performing its function optimally, while water stress and protein degradation also contributed to the decrease of PPO activity in leaves. This may be the reason for the decrease of enzyme activity in late withering [44,49]. Jiang et al [28] showed that the increase and then decrease in PPO activity was not completely consistent with the change trend found in this study, which might be related to variety, season and appellation.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Additionally, the organic acids accumulated continue to reduce pH late in the withering stage, which prevented the enzyme from performing its function optimally, while water stress and protein degradation also contributed to the decrease of PPO activity in leaves. This may be the reason for the decrease of enzyme activity in late withering [44,49]. Jiang et al [28] showed that the increase and then decrease in PPO activity was not completely consistent with the change trend found in this study, which might be related to variety, season and appellation.…”
Section: Discussioncontrasting
confidence: 54%
“…Interestingly, exploring the changes in key endogenous enzymes that affect the flavor components of black tea is helpful to improve its flavor. PPO is a metalloenzyme with type III copper as its core, which is abundant in nature [44]. Compared to POD and glucosidase, PPO, which can catalyze the oxidation of catechins to theaflavins and thearubigins as well as the enzyme coupled oxidation of aromatic precursors [45], plays an important role in the catalysis of flavonoids during tea processing [46].…”
Section: Discussionmentioning
confidence: 99%
“…Withering is a crucial physical and biochemical preconditioning step in the production of black tea. During the withering process, fresh tea leaves not only lose moisture and become flexible, but the activity of various enzymes that catalyze the conversion of volatile and nonvolatile components increases [39,46], and synergistically promotes the formation of tea flavor quality [47]. Moreover, OAVs of citronellol, methyl cyclohexanecarboxylate, linalool, p-cymene, and (E)-linalool oxide (furanoid) are the top five in all samples, indicating its essential role in aroma formation.…”
Section: The Formation Of the Sweet And Citrus-like Aroma During Scbt...mentioning
confidence: 98%
“…Effect of enzyme-catalyzed processing on tea metabolites Tea leaves can accumulate catalytic proteins (i.e., enzyme), of which hydrolases (e.g., amylase and β-glycosidase) and oxidoreductases (e.g., polyphenol oxidase, peroxidase, and lipoxygenase) are the major endogenous enzymes involved in tea manufacturing (Tang et al, 2023). During the pro-cessing of white, oolong, and black teas, the driving force of metabolite variation is related to the biochemical reactions involving the endogenous enzymes.…”
Section: 31mentioning
confidence: 99%